Is quantity or quality of food influencing the reproduction of rice-field rats in the Philippines? - Htwe, Nyo Me; Singleton, Grant R. (Commonwealth Scientific and Industrial Research Organisation, 2014)
Context Asynchronous or aseasonal planting of rice crops can extend the period when high-quality food is available to rodents. Consequently, rodents may extend their breeding season, increasing population densities. An improved understanding of the effects of food availability and quality on rodent reproduction may enable better forecasts of high rodent population densities in response to asynchronous or aseasonal planting of crops. Aim The present study examined the association between the quality and quantity of food and the reproductive success of female rice-field rats, Rattus tanezumi and Rattus argentiventer, in a lowland rice landscape in the Philippines. Methods We evaluated the main dietary components of female rats on two different islands through a cropping season during the 2010 wet season. The breeding performance of 60 female R. tanezumi and 60 R. argentiventer individuals was measured. Key results Our findings indicated the following: (1) the main dietary items for females of both rodent species during the main breeding season (the booting stage to harvest) were rice panicles and rice seeds; (2) the high protein content of the rice crop at the tillering stage triggered the onset of the main breeding season, leading to the highest rates of conception during the booting and ripening stages; (3) the quantity of food available at the stubble stage provided sufficient nutrient to maintain pregnancy and lactation by females; and (4) asynchronous planting and poor harvest technology could extend the breeding season of rice-field rats. Conclusions We contend that the extension of the growing season by 3–4 weeks provides high-quality food for rodents, which in turn provides sufficient conditions for higher population densities. The availability of spilled rice grain at the stubble stage is a source of good-quality food for pregnant and lactating females, allowing extension of the breeding season. Implications Synchronous planting (within 2 weeks) with good post-harvest management of rice stubble are important to prevent high population densities of rice-field rats in lowland rice landscapes in the Philippines.